Digitalisasi Rumah Baca: Akselerasi Literasi Masyarakat Pesisir Kampung Della Papua Barat Daya - Achmad Rusdi; Ihsan Febriadi; Heriyanti Heriyanti; Renny Purnawati; Muh. Mawardi; Miseri Cordias Bisulu; Said Samsaman; Amos Nikodemus Aibini; Andi Teis Umpes; Novita Fenetiruma; Krristina Claura Monika Mambyeuw; Hadra Tuljanna Sulaiman (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
The Reading House digitalization program seeks to strengthen literacy capacity among coastal communities in Kampung Dela by integrating technology into collection management and learning services. Activities included outreach sessions, hands-on training, and ongoing mentoring focused on digital library applications, book catalog systems, and service standard operating procedures. Program effectiveness was measured through pretest and posttest assessments administered to 20 participants across seven key indicators. Results revealed substantial gains, with mean scores rising from 30–40 points at baseline to 82–92 points post-intervention. Such improvements reflect enhanced participant competency in digital literacy, collection management practices, and willingness to sustain Reading House operations. Digitalization has successfully repositioned the Reading House as an inclusive, technology-responsive non-formal learning hub. This program offers a replicable framework for advancing digital literacy in geographically isolated coastal regi.